SUN-445 A Brazilian Multicentric Study Evaluating Pregnancies Induced by Cabergoline in Patients Harboring Prolactinomas - Sant Anna, Beatriz (J Endocr Soc, 2019)
BACKGROUND: Prolactinoma is the most common pituitary tumor and a frequent cause of infertility. Treatment with dopamine agonists (DA) usually reverse hyperprolactinemia and hypogonadism, subsequently allowing pregnancy. Cabergoline (CAB) presents a higher affinity to dopamine receptor type 2, better tolerance and more effectiveness than bromocriptine (BCR). Nevertheless, due to the larger experience and its shorter half-life, comparing to CAB, BRC is still the drug of choice to induce pregnancy. Although studies did not show higher rates of maternal and fetal complications in CAB induced-pregnancies, an increase in published data is needed to confimr the drug safety. OBJECTIVE: To evaluate maternal-fetal outcomes of CAB-induced pregnancies in patients with prolactinoma in a large Brazilian cohort. PATIENTS AND METHODS: A Brazilian multicentric retrospective study assessed the outcomes regarding tumor expansion, abortion, preterm, low birth weight, congenital malformations and neuropsychological development of children from women with prolactinomas treated with CAB at the time of conception and/or during pregnancy. Breastfeeding safety and tumor remission after delivery were also reported. RESULTS: We included 194 women, median age of 31 (17-45) yrs, with prolactinomas, 46% microadenomas (MIC) and 54% macroadenomas (MAC), resulting in 233 pregnancies in which CAB was used. The drug was withdrawal after pregnancy confirmation in 89% of patients at a median gestation age of 6 (2-36) weeks. Symptoms secondary to tumor growth occurred in 22 cases, more frequently in MAC (23%) than MIC (7%) (p=0.005), being DA reintroduced in 21 patients. Neurosurgery was performed in six patients, five without tumor control with medical treatment. Abortion rate was 11%. From live-birth deliveries, preterm occurred in 12%, low birth weight in 6% and congenital malformations in 3%. Impared neuropsychological development was reported in 7% of 145 children, one to 228 months of age. Twenty-two pregnancies are still ongoing. After one year of delivery, tumor imaging and prolactin reassessment showed remission in 22% of cases, unrelated to breastfeeding or tumor size. DISCUSSION: Due to its longer half-lime, as compared to BRC, CAB use in pregnancy is stiil a matter of concern. Our findings are in agreement with previous studies evaluating maternal and fetal outcomes in pregnancies induced by CAB. In our cohort and in the majority of cases in those studies, CAB was usually withdrawal after pregnancy confirmation. Additionally, tumor remission rate was similar to literature data. CONCLUSIONS: Our multicentric study, including 233 pregnancies, significantly increased the number of reported cases, reassuring CAB safety for pregnancy, induction in women harboring prolactinomas.